Gender play in Mark Twain cross-dressing and transgression - Morris, Linda (Mark Twain and his circle series., 2007)
"Explores Mark Twain's use of cross-dressing across his career by exposing the cast of his characters who masqueraded as members of the opposite sex or who otherwise defied gender expectations. Morris grounds her study in an understanding of the era's theatrical cross-dressing and changing mores, and events in Clemens's own household"--Provided by publisher.